2D-1D crossover from quantum well to quantum wire behaviour in GaAs v-groove structures - Roshan, R; Cade, N; Maciel, A; Ryan, J; Schwarz, A; Schapers, T; Luth, H (2002)
he distribution of electron current in GaAs AlGaAs v-groove quantum wire structures with groove widths varying from 1 to 25 mum has been studied using far- and near-field spectroscopy techniques. We find clear evidence of the formation of 'corner' quantum wires in wide grooves which coalesce to form single wires in grooves with widths narrower than similar to 5 mum. Spatially resolved photoluminescence measurements in the presence of an applied voltage provide information about the distribution of current in the device. (C) 2002 Elsevier Science B.V. All rights reserved.